THE URGENCY OF ECONOMIC EMPOWERMENT IN REALIZING LEGAL PROTECTION FOR CHILD VICTIMS OF SEXUAL VIOLENCE - Syaiful Asmi Hasibuan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Sexual violence not only causes momentary suffering but can also impact every aspect of a victim's life. The resulting trauma often affects the victim’s psychological, social, and emotional well-being in the long term and can even lead to a loss of hope and self-confidence needed to resume a normal life. Sexual violence must be understood as a serious issue because it not only harms individual victims but also has the potential to threaten the quality of a nation’s human resources and the sustainability of future generations. This study examines the urgency of economic empowerment in realizing legal protection for child victims of sexual violence. This study employs a normative legal research method through a literature review, utilizing secondary data from primary, secondary, and tertiary legal sources. This study finds that economic empowerment for child victims of sexual violence is expected to improve the victims’ living conditions through various efforts that support the enhancement of their quality of life, independence, and well-being. In this context, economic empowerment can be understood as an effort to build and strengthen the economic capacity of child victims and their families, giving them greater opportunities to lead better lives in the future. One form of economic empowerment that can be provided to child victims of sexual violence is support in the form of capital assistance. Access to capital is one of the most common obstacles faced by individuals who possess the talent, ability, and desire to become entrepreneurs. Providing capital support can be an effective means to help child victims develop their economic potential, increase their independence, and build a more prosperous future as part of legal protection efforts focused on the recovery and sustainability of their lives.